Mr. Wolf's class. Mystery club - Steinke, Aron Nels (New York : Graphix, 2019)
Mr. Wolf's students are settling into their new classroom, and Randy, Aziza, and Margot realize they have some questions . . . To answer these questions, the three friends start a mystery club!
Booklist, February 2019
Kirkus Review, January 2019
3.7
3-6
GN490L
Keywords: Elementary school teachers -- Comic books, strips, etc. -- Fiction; Schools -- Comic books, strips, etc. -- Fiction; Friendship -- Comic books, strips, etc. -- Fiction; Elementary school teachers -- Juvenile fiction; Schools -- Juvenile fiction; Friendship -- Juvenile fiction; Humorous stories; Humorous comics; Graphic novels; Graphic novels